The Characteristics of Pregnant Women with Anemia at Puskesmas Sanden Working Area in 2022-2023 - Dewantari, Aulia Yasmin; Sistharani, Naila; Yuniasih, Dewi; Laariya, Tira Alfiani; Mawardi, Fitriana; Suprabandari, Suprabandari; Rahmawati, Nurul Fauziyah (Ahmad Dahlan Medical Journal, 2023)
Anemia in pregnancy is a public health problem especially in developing countries and is associated to adverse pregnancy outcomes. The prevalence of anemia in Indonesia is relatively high. In 2018, the prevalence of anemia reached 32%. While the prevalence of anemia in pregnant women was 48.9% in the same year. Reducing the incidence of anemia in pregnant women is included in efforts to reduce maternal mortality (MMR) and morbidity or mortality in babies born. Puskesmas Sanden has a program to reduce MMR and infant mortality with one of the efforts made is to reduce the number of anemias in pregnant women. The purpose of this study was to determine the prevalence and characteristics of pregnant women who experience anemia in the working area of Puskesmas Sanden. This research was conducted using a descriptive method. The data were taken from secondary data, namely register data for pregnant women who carried out examinations at the Mother and Child Health Polyclinic in Puskesmas Sanden. The research respondents were all pregnant women who experienced anemia from January 1st, 2022 to June 30th, 2023, in which, there were 120 research respondents. Research variables include mother's age, number of parities, and upper arm circumference (UAC). The results showed that the prevalence of anemia in pregnant women was 254 people. The characteristics of pregnant women who experience anemia based on age showed that there were 97 people (80.83%) pregnant women who experience anemia are dominated by women aged 21-34 years old, while there are 3 (2.5%) pregnant women with anemia aged ≤ 20 years old, and 20 pregnant women with anemia aged ≥ 35 years (16.67%). Meanwhile, based on the number of parities, in this study, the total parity of all pregnant women who were included in the research respondents was ≤ 3, which were 120 people (100%), and none of the pregnant women who had parity > 3. Then, based on UAC, there were 94 (78.33%) pregnant women with anemia had more UAC ≥ 23.5 cm, and as many as 26 pregnant women with anemia had UAC < 23.5 cm (21.67%). The conclusion of this study is that the prevalence of pregnant women at Puskesmas Sanden is still relatively high, which is 39.69%.